A Study Of Consumer’s Perception Towards Online Shopping For Mobile Phones - A Case Study of Tenkasi District. (International Journal of Food and Nutritional Sciences, 2022)
Technology plays an eminent role in the connectivity of humans with the world. Mobile phones play a vital role in it. The dependence of the world on the internet has grown so much that internet connection seems like the fourth basic need of the humans. The Internet has emerged as a boon to mankind. The internet has spurred a transformation in many aspects of life. It is one of the biggest contributions in making the world a global village. The use of the internet has grown tremendously since it was introduced due to its flexibility and ease of access. In the present scenario information, including access to the internet has become the basis for personal, economic and political advancement. The present study is initiated to analyse the significant difference in consumer’s perception towards online shopping for Tenkasi District. The researchers constructed a strong questionnaire and distributed it to 180 respondents in the study area. The researcher received 150 fully completed questionnaires from the respondents.